Profiling of metabolic alterations in mice infected with malaria parasites via high-resolution metabolomics - Chhibber-Goel, Jyoti; Shukla, Anurag; Shanmugam, Dhanasekaran; Sharma, Amit (Molecular and Biochemical Parasitology, 2022)
Background: Malaria infection can result in distinct clinical outcomes from asymptomatic to severe. The association between patho-physiological changes and molecular changes in the host, and their correlation with severity of malaria progression is not fully understood. Methods: In this study, we addressed mass spectrometry-based temporal profiling of serum metabolite levels from mice infected with Plasmodium berhgei (strain ANKA). Results: We show global perturbations and identify changes in specific metabolites in correlation with disease progression. While metabolome-wide changes were apparent in late-stage malaria, a subset of metabolites exhibited highly correlated changes with disease progression. These metabolites changed early on following infection and either continued or maintained the change as mice developed severe disease. Some of these have the potential to be sentinel metabolites for severe malaria. Moreover, glycolytic metabolites, purine nucleotide precursors, tryptophan and its bioactive derivatives were many fold decreased in late-stage disease. Interestingly, uric acid, a metabolic waste reported to be elevated in severe human malaria, increased with disease progression, and subsequently appears to be detoxified into allantoin. This detoxification mechanism is absent in humans as they lack the enzyme uricase. Conclusions: We have identified candidate marker metabolites that may be of relevance in the context of human malaria.
Keywords: Host response; Infectious diseases; malaria; metabolite; Plasmodium